High-pressure and high-temperature modulation of one-dimensional infinite chain in SeO2 - Lu, Wencheng; Liu, Siyu; Cai, Jinqun; Ning, Ping; Ma, Chuanheng; Liu, Guangtao; Wang, Hongbo; Guo, Qing; Zhou, Mi; Wang, Yanchao; Ma, Yanming (Applied physics letters, 2024)
The structural evolution of lone-pair compounds under high-pressure and high-temperature conditions has been a subject of fundamental interest in revealing modulated polymorphs. As one of the archetypal lone-pair compounds, selenium dioxide (SeO2) has attracted much attention due to the pressure modulation of its one-dimensional infinite W-shaped chain arrangement. Here, through swarm intelligence algorithm in conjunction with the first-principles simulation, we propose the existence of an orthorhombic Pnma-SeO2 structure, characterized by V-shaped chains interconnected via vertex-sharing SeO3 pyramids. These V-shaped chains demonstrate reduced compressibility along their chain direction compared to the W-shaped chains. Calculations indicate that Pnma-SeO2 is a semiconductor with a large indirect bandgap of 2.39 eV. Remarkably, we synthesized the predicted Pnma-SeO2 in a laser-heated diamond anvil cell at a pressure of 48.5 or 87 GPa as identified by in situ synchrotron x-ray diffraction data. Our findings lead to a significant extension of the phase diagram and transition path of SeO2 and provide key insights into understanding the pressure modulation in lone-pair compounds.